PKM Kelompok Ibu-Ibu Rumah Tangga dalam Pembuatan Aneka Kue Corona Cookies Pada Situasi Pandemi Covid-19 - Haerani Haerani; Besse Qurani (Seminar Nasional Pengabdian Kepada Masyarakat, 2020)
Training on making Corona Cookies for housewives in Batu-Batu, Marioriawa District, Soppeng Regency is a community partnership program (PKM) as a solution to the needs of housewives to provide knowledge and skills. The training participants were 10 housewives in Batu-Batu and in Lejja. The training method is carried out in the form of lectures, questions and answers and practice. This PKM program aims to: 1) understand more about knowledge and skills in making Corona Cookies, 2) practice making Corona Cookies properly, 3) increase entrepreneurial motivation with a variety of Cookies that have never existed in Batu-Batu, Marioriawa District, Soppeng Regency . After carrying out the PKM activities of the household housewives group in the making of corona cookies cakes in the pandemic COVID-19 situation, it can be concluded that as many as 10 participants have understood well how to make Corona Cookies. Furthermore, as many as 10 participants were skilled in making various Corona Cookies and were also motivated by the importance of empowering housewives through training in making Cookies in a sustainable manner